How Does AI Improve Medical Education? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2017)
The integration of artificial intelligence (AI) is revolutionizing the healthcare sector, and its impact is extending into medical education. AI is reshaping...
Keywords: AI in Medical Education and Future of Healthcare; Improve; Medical; Education; Artificial Intelligence; Healthcare